2019
DOI: 10.1111/ina.12538
|View full text |Cite
|
Sign up to set email alerts
|

Wood stove use and other determinants of personal and indoor exposures to particulate air pollution and ozone among elderly persons in a Northern Suburb

Abstract: A six‐month winter‐spring study was conducted in a suburb of the northern European city of Kuopio, Finland, to identify and quantify factors determining daily personal exposure and home indoor levels of fine particulate matter (PM2.5, diameter <2.5 µm) and its light absorption coefficient (PM2.5abs), a proxy for combustion‐derived black carbon. Moreover, determinants of home indoor ozone (O3) concentration were examined. Local central site outdoor, home indoor, and personal daily levels of pollutants were moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…The results of the study presented here are consistent with other groups that have investigated air quality relationships between outdoor and indoor environments where older adults reside. Residential studies in homes of older adults over a 6 months period demonstrate a high correlation between ambient and indoor particulate exposure measured by gravimetric techniques 4,19 . Similar results were also seen in a 12 days study conducted in a retirement community, where Buczynska et al found no significant indoor sources of air pollution but did see a positive relationship between outdoor and Indoor Air Quality 5 .…”
Section: Discussionsupporting
confidence: 57%
“…The results of the study presented here are consistent with other groups that have investigated air quality relationships between outdoor and indoor environments where older adults reside. Residential studies in homes of older adults over a 6 months period demonstrate a high correlation between ambient and indoor particulate exposure measured by gravimetric techniques 4,19 . Similar results were also seen in a 12 days study conducted in a retirement community, where Buczynska et al found no significant indoor sources of air pollution but did see a positive relationship between outdoor and Indoor Air Quality 5 .…”
Section: Discussionsupporting
confidence: 57%
“…However, indoor air pollution attributed to the use of wood burning as a heating system is linked to a lower performance of the interviewed participants, particularly in the number of errors committed in the inhibition condition of the A-HSCT. This negative correlation could be due to the exposure of individuals to air pollutants resulting from wood burning chemical reactions, as mentioned in various studies, particularly CO2 inhalation that is anxiogenic and deleterious for executive functions [41,42]. In contrast, participants who use electricity as a source of heating in their households performed better in terms of response-time in the inhibition condition of our test, which goes in line with the result mentioned above.…”
Section: Heating System and Air Pollutionsupporting
confidence: 90%
“…However, indoor air pollution attributed to the use of wood burning as a heating system is linked to a lower performance of the interviewed participants, particularly in the number of errors commited in the inhibition condition of the A-HSCT. This negative correlation could be due to the exposure of individuals to air pollutants resulting from wood burning chemical reactions, as mentioned in various studies, particularly CO2 inhalation that is anxiogenic and deleterious for executive functions 41,42 . In contrast, participants who use electricity as a source of heating in their households performed better in terms of response-time in the inhibition condition of our test, which goes in line with the result mentioned above.…”
Section: Heating System and Air Pollutionmentioning
confidence: 94%